Development of a vacuum arc thruster for nanosatellite propulsion - Lun, Jonathan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.